The Effectiveness of Religious Extracurricular Programs in Shaping Students’ Character" - Hidayatullah; Wiwik Dyah Andayani (Journal of Science and Education (JSE), 2025)
This study aims to analyze the effectiveness of religious extracurricular programs in shaping students’ moral character at two public senior high schools: SMA Negeri 1 Tegalwaru and SMA Negeri 1 Pangkalan Karawang. Using a qualitative approach with a comparative case study design, data were collected through participatory observation, in-depth interviews, and document analysis. The findings reveal that both schools implement adaptive yet distinct program designs: SMA Tegalwaru emphasizes face-to-face approaches based on modeling and habituation, while SMA Pangkalan Karawang integrates digital platforms, preaching projects, and parental collaboration. Character development takes place effectively through mentoring sessions that involve reflective dialogue and emotional student engagement. Key success factors include convergent support from schools, families, and communities, as well as the availability of physical and digital infrastructure. This study proposes the Dynamic Spirituality Development Model, which combines adaptive content delivery, linguistic-ritual value reinforcement, and community-based evaluation. The findings highlight the importance of contextual program design, dialogical mentoring strategies, and ecosystem synergy in strengthening students’ religious character in the digital age.